IMS crash course - Shepard, Steven (McGraw-Hill, 2006)
Written by a renowned professional author and educator with 25 years of experience in the telecommunications industry, IMS Crash Course gives you a broad perspective on why IMS evolved, how the technology works, its system requirements, and potential regulatory issues—all in one convenient package. If you are looking to make sense of this breakthrough technology, its benefits, and its real-world implementations, read this book first.